Youth program activity impacts: A model of camp activities, psychological needs, and immersion. (February 2021) - Ellis, Gary; Jiang, Jingxian; Locke, Darlene; Snider, Cari
Highlights: Immediate experiences during youth activities may facilitate development. Immersion is the mechanism through which immediate experiences promote development. Immersion results from satisfaction of psychological needs. Psychological need satisfaction results from optimal challenge and intrinsic motivation. Activities can be structured to facilitate optimal challenge and intrinsic motivation. Abstract: We examined linkages through which structured camp experiences may facilitate satisfaction of psychological needs and thereby contribute to expansion of the self. First, we tested the effects of "leveling-up" the challenges of activities with the skills of campers and camper motivation source (intrinsic, integrated, introjected, and extrinsic) on immediate psychological need satisfaction during each of eight camp activities (archery, crafts, dancing, fishing, kayaking, riflery, rock wall climbing, and swimming). Then, we tested relations between psychological need satisfaction and the subjective experience, immersion. Immersion, theoretically, yields expansion of the self. Campers ( n = 150, ages 11–13, co-recreational) reported their sense of autonomy, competence, and relatedness, and degree of immersion immediately following each of the eight camp activities. The hypothesized causal sequences were supported by the data. Camper motivation source and leveling-up the challenge-skill structure of immediate camp experiences yielded psychological need satisfaction. Psychological need satisfaction, in turn, increased immersion.